Acquired alpha-thalassemia in association with myelodysplastic syndrome and other hematologic malignancies. - Steensma, D; Gibbons, R; Higgs, D (2005)
Abnormalities of hemoglobin synthesis are usually inherited but may also arise as a secondary manifestation of another disease, most commonly hematologic neoplasia. Acquired hemoglobin disorders can be seen in any population and are not restricted to areas of the world with high incidences of inherited hemoglobinopathies. In fact, the acquired hemoglobinopathies may be more readily recognized where inherited hemoglobin abnormalities are rare and less likely to cause diagnostic confusion. Acquired alpha-thalassemia is the best characterized of the acquired red blood cell disorders in patients with hematologic malignancy, and it is almost always associated with a myelodysplastic syndrome (MDS). At least 2 molecular mechanisms for acquired alpha-thalassemia are now recognized: acquired deletion of the alpha-globin gene cluster limited to the neoplastic clone and, more commonly, inactivating somatic mutations of the trans-acting chromatin-associated factor ATRX, which cause dramatic down-regulation of alpha-globin gene expression. Here we review the clinical, hematologic, and molecular genetic features of alpha-thalassemia arising in a clonal myeloid disorder, and we discuss howATRX might affect gene expression in normal and abnormal hematopoiesis through epigenetic mechanisms.